Procesamiento del potencial P300 para el desarrollo de una interfaz cerebro-computadora. - Gualán Carchi, Franklin Iván (2018)
In the present work an alternative mechanism for the implementation of electroencephalography focused on the investigation and implementation of Brain-Computer Interfaces (BCI) is studied and developed, beginning with a qualitative analysis of the existing devices for these purposes and establishing an alternative in the base to the technical characteristics that are required for the development of a BCI, in addition to the base of the theory and the practice of the development of algorithms of signal processing in the time-frequency domain for the detection of P300 potential. The part of the software that corresponds to the acquisition device is developed in a free platform (Python), while the processing algorithms are carried out in SIMULINK, finally the results of the acquisition system of the processing algorithms are compared with works of proven validity.